2022
DOI: 10.1101/2022.12.01.518674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crosstalk of platelets with macrophages and fibroblasts aggravates inflammation, aortic wall stiffening and osteopontin release in abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a highly lethal disease with progressive dilatation of the abdominal aorta accompanied by degradation and remodelling of the vessel wall due to chronic inflammation. Platelets are small anuclear cells that can release various inflammatory cytokines and biological response modulators when activated. In cardiovascular diseases, platelets are crucial for the inflammatory response but their role in AAA is poorly understood. However, both -experimental and clinical data- strongly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…To further investigate the impact of platelet–RBC interactions and the procoagulant activity of these cells, we analyzed platelet–RBC interactions and procoagulant activity in an experimental mouse model of AAA (the pancreatic porcine elastase [PPE] model) and in patients with AAA. We recently detected elevated platelet activation and platelet-mediated inflammation in mice and patients with AAA (26). Here, histological analysis at day 28 after elastase infusion revealed that platelets and RBCs had migrated into the abdominal aorta of PPE mice (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the impact of platelet–RBC interactions and the procoagulant activity of these cells, we analyzed platelet–RBC interactions and procoagulant activity in an experimental mouse model of AAA (the pancreatic porcine elastase [PPE] model) and in patients with AAA. We recently detected elevated platelet activation and platelet-mediated inflammation in mice and patients with AAA (26). Here, histological analysis at day 28 after elastase infusion revealed that platelets and RBCs had migrated into the abdominal aorta of PPE mice (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%